Conveying Missed Miscarriage Information at Obstetric Ultrasounds: Patient Experiences and Trauma-Informed Considerations - Rana Van Tuyl DSocSci; Kathryn Berry-Einarson MPH (Journal of Patient Experience)
Health system changes are needed to improve the care of people experiencing miscarriage, including patients receiving missed miscarriage information at obstetric ultrasounds. This study included policy research on prenatal care guidelines, policy research on employment legislation for bereavement leave, interviews with people who had lived/living experience with miscarriage recovery in British Columbia, Canada, and a dialogue with patients. Missed miscarriages are commonly diagnosed during routine obstetric ultrasounds, requiring ultrasound technicians and other healthcare providers to communicate missed miscarriage information to patients. Compassionate care and communication are needed to support patients and partners during this often-difficult time. Trauma-informed training should be provided to ultrasound technicians and other healthcare providers who communicate information on miscarriage to patients in clinics and hospitals, including emergency departments. Additionally, health systems can consider policy recommendations discussed in this article to place trauma considerations at the center of the patient/provider experience, such as allowing a support person to be present during the full duration of the obstetric ultrasound and inviting the patient to make the decision on receiving, or not receiving, the ultrasound picture.